Pemberdayaan Karang Taruna dalam Pencegahan Penyebaran Covid-19 di Desa Wonokerto Kecamatan Wonogiri - Sugiyarto Sugiyarto (Poltekkes Kemenkes Surakarta, 2020)
Background: Corona Virus Disease-19 (COVID-19) is an infectious disease caused by the SARS-COV 2 virus or Corona Virus. COVID-19 is declared as a world pandemic by WHO and is determined by the Government as a non-natural disaster in the form of disease outbreaks that needs to be taken integrated countermeasures including the involvement of all components of the community. The purpose of community service activities in the form of empowering youth groups in preventing the spread of covid-19 in Timang Kulon Village Wonokerto Wonogiri Village is expected to increase the understanding and knowledge of cadets related to preventing the spread of covid-19 so as to contribute to preventing the spread of covid-19 in Timang Kulon, Wonokerto, Wonogiri. Methods: Health education and Pasting the Covid-19 prevention posters in public places and distributing masks to the public. Results: The results of the post-test assessment showed that there was an increase in the knowledge of youth groups from 73% to 95% after health counseling. Conclusion: The knowledge of youth organization has increased and this activity requires follow-up, i.e. monitoring community behavior related to preventing the spread of Covid-19.